Analysis of the urban heat island intensity based on air temperature measurements in a renovated part of Budapest (Hungary) - Dian, Csenge; Pongrácz, Rita; Incze, Dóra; Bartholy, Judit; Talamon, Attila (Geographica Pannonica, 2019)
The ratio of buildings, streets, and other artificially covered areas are increasing in cities. Ferencváros is an inner district of Budapest, the capital city of Hungary. For the local government of the district it is an important goal in the framework of the urban development planning to increase the proportion of vegetation since green areas have a mitigating effect for the urban heat island (UHI) intensity. We carried out an in situ measurement program for air temperature and relative humidity with 24 measuring points in Ferencváros, and also completed a green area survey in the renovated part of the district. The main aim of this paper is to analyse the daily cycle and the spatial structure of the UHI intensity based on air temperature.
Keywords: spatial structure of UHI; daily cycle of UHI intensity; in situ measurements; green area; summer; autumn